Narrativas sobre a metrópole centenária: Simmel, Hessel e Seabrook - Fortuna, Carlos (2011)
Georg Simmel’s The Metropolis and Mental Life is treated as a seminal study of urban sociology and of the analysis of human behavior in metropolitan contexts. A relationship between the blasé attitude and the appearance of the flâneur is established. The latter is seen through Franz Hessel’s writings, in the late 1920s, which present a somewhat romantic view of the pre World War II in Europe. The article ends up by questioning whether flânerie still exists in today’s global South megacities. The author makes use of J. Seabrook’s recent writings to show the deep transformation Simmel’s metropolis went through in the past hundred years. If we can still talk of flânerie, it has certainly undergone a very radical change in nature which leads to an epistemic revision of the canon in urban sociology.